Urban forestry and urban greening for sustainable urban development-A case of Dhaka north city corporation area (Zone-1) - Roy, S; Dutta, S; Hoque, MM (Journal of the Bangladesh Agricultural University, 2017)
Urban forestry and urban greening is one of the most substantial factors for sustainable urban development, which can contribute towards good quality of life and sound environment. Dhaka, the capital of Bangladesh once renowned for its green resources but in recent times the city is losing its greeneries very rapidly. This study was intended to explore the status of urban greening as well as to investigate the prospects and challenges for enhancing urban forestry and urban greening in Dhaka North city corporation area (Zone-1). This study focused on the qualitative approach where interview with key informants, questionnaire survey and observation techniques were followed to obtain required information. The study identified some factors that are responsible for losing of green resources in Dhaka city including transformation of existing green areas or open spaces to other land use purposes, unplanned urbanization & improper planning, rapid increase of urban population and lack of conservation activities for protecting the existing greeneries. The study also revealed that still there are ample opportunities to enhance the greeneries in Dhaka city by conserving the existing green areas (e.g. parks, gardens, playgrounds etc.), increasing roadside plantation, promoting homestead and rooftop gardening and by initiating afforestation and nursery activities. J. Bangladesh Agril. Univ. 14(2): 167-176, December 2016